Phenomenographic Approaches in Research About Nursing - Martha M. Whitfield; Mike Mimirinis; Danielle Macdonald; Tracy Klein; Rosemary Wilson (SAGE Publishing, 2023)
We propose that phenomenography is well-suited to research about nursing, given its focus on identifying variation in individuals' experiences, and inclusion of diverse voices and perspectives. Phenomenography explores qualitatively different ways in which a group of people experience a phenomenon, often using semi-structured interviews. The use of phenomenography is especially relevant in research about nursing which provides accounts of the experiences of nurses and patients within complex practice settings. We consider the tenets of phenomenography and examine phenomenography's relationship to and differences from phenomenology. We review literature published about phenomenographic research in nursing and reflect on the potential benefits of phenomenographic research about nursing. This paper adds to knowledge about use of phenomenography in research about nursing.